(untitled) (Fiep Bulletin - online, 2013)
The physical and psychological training when work integrating body and mind, considering the individual as a whole. Objective: To examine whether there is any significant difference between levels of stress and strength of lower limbs in pre-and post-test, after an intervention by a physical and psychological training in dancers. Methodology: The sample consisted of 11 jazz dancers, of both sexes, aged between 18 and 23, members of a dance company from the city of Curitiba-PR. To collect the data testing of Vertical Thrust to assess the strength and Inventory Scale Stress Understood were applied before and after the training. The training had duration of 7 weeks. For the processing of the data analysis, a descriptive statistics (mean and standard deviation) was used, a MANOVA at a level of significance p <0.05 and a correlation of Pearson. Results and conclusion: For the stress, in the pre-test, 100% of individuals had levels of stress above the U.S. population, and 54.54% above the average for the southern Brazil population. The group’s average of 22.63 (SD=6.07). In the post-test, 100% of individuals had values above the U.S. average and 37.50% above the southern Brazilian population. The average group in the post-test was 20.50 (SD=3.92). There was no significant difference in the perception of stress between pre and post-test F(2,11)=1595, p=0.225. For strength, the dancers in the pre-test performed more than 80%. In the post-test, 100% performed between 90 and 100%. There was significant difference between pre-and post-test F(2,11)=7332, p=0,016. The results of the correlation between the two variables were moderately negative and showed no significant difference (r=-0144, p=0.570). It is possible to be concluded from this study, that the stress and strength of the lower limbs are inversely proportional, that is, the shorter the levels of stress, the higher the performance in tests of strength. It was found that the intervention of reduction of stress was not as efficient as the training of strength. In this sense, it is necessary to use various techniques to reduce stress to increase the performance of the dancers. It is suggested further studies with different populations and age groups to monitor the performance and stress reduction.